Penerapan Teori Belajar Behavioristik dalam Proses Pembelajaran PAI - Akbar, Fathir; Gantaran, Abyan (Darajat: Jurnal Pendidikan Agama Islam, 2022)
The rapid development of global technology provides a challenge for education to contain its negative impact on the development of children's behavior. PAI teachers as the main figures for the formation of students' morals must master science and learning theory. Behavioristic learning theory as a solution to change the behavior of students who seem deviant. This research uses literature or literature studies (library research) and uses content analysis (content analysis) as the knife. This research results, that behavioristic theory is very relevant to be applied in the learning process of Islamic Religious Education because it is aligned with the goals of Islamic Religious Education teachers in order to change students' behavior for the better. Learning Islamic Religious Education is felt to be compatible with behavior theory because almost every competency in PAI learning material emphasizes changing attitudes. The application of behavioristic theory has been widely applied in PAI learning using reinforcement, motivation, stimulus, and training methods. The application of this theory succeeded in changing the behavior of students in a positive direction.